2021
DOI: 10.18805/ag.d-5236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Quantity of Iron Oxide Nanoparticles on Growth, Haematological and Biochemical Characteristics of Koi Carp

Abstract: Background: Nanoparticles such as Se, Cu, Fe, FeO, Zn and ZnO play a vital role in aquaculture operations and are essential microminerals to enhance fish growth. The dietary supplementation of nanoparticles produces better survival, growth, antioxidant levels and immunity in aquatic organisms. The present work aimed to evaluate the different quantity of Iron oxide nanoparticles on the Growth, Haematological and Biochemical Characteristics of Koi carp. Methods: Iron oxide nanoparticles were synthesized and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The assimilation and metabolism of zebrafish were higher in feed V and feed IV respectively. Sangeetha and Rajan (2021) [25] reported that the assimilation of Koi carp was higher in feed IV containing 30 mg of iron oxide nanoparticles in the feed. The gross growth efficiency of zebrafish was higher in feed III containing 40 mg of ZnO NPs in feed.…”
Section: Discussionmentioning
confidence: 99%
“…The assimilation and metabolism of zebrafish were higher in feed V and feed IV respectively. Sangeetha and Rajan (2021) [25] reported that the assimilation of Koi carp was higher in feed IV containing 30 mg of iron oxide nanoparticles in the feed. The gross growth efficiency of zebrafish was higher in feed III containing 40 mg of ZnO NPs in feed.…”
Section: Discussionmentioning
confidence: 99%
“…The assimilation and metabolism of tilapia reared in feed V were higher. The assimilation of Koi carp was higher in feed IV containing 30 mg of iron oxide nanoparticles in the feed [12]. The gross and net growth efficiency of tilapia reared in feed III was higher.…”
Section: Figure 6 Condition Factor (K) Of Tilapiamentioning
confidence: 92%
“…50,51 It has been proved in aquatic feeding that dietary supplementations of Fe in nanoforms induced nutritional beneficial effects in aquatic species. [52][53][54][55][56][57] For example, enhanced growth performance and alkaline phosphatase activity were observed within goldfish (C. auratus), which received a Fe-NPs-containing diet (0.5 g/kg) for 60 days. 52 In addition, dietary Fe-NPs supplement (20 mg/kg) for a 90-day experimental trial showed an improvement in growth response, digestive enzyme function, food intake, better survival, and growth of M. rosenbergii post larvae.…”
Section: Fe-npsmentioning
confidence: 99%
“…Fe deficiency was found to cause hypochromic microcytic anaemia in brook trout ( Salvelinus fontinalis ) and common carp ( Cyprinus carpio ) 50,51 . It has been proved in aquatic feeding that dietary supplementations of Fe in nanoforms induced nutritional beneficial effects in aquatic species 52–57 . For example, enhanced growth performance and alkaline phosphatase activity were observed within goldfish ( C. auratus ), which received a Fe‐NPs‐containing diet (0.5 g/kg) for 60 days 52 .…”
Section: Applications Of Inorganic Nps In Aquaculturementioning
confidence: 99%
See 1 more Smart Citation